2006
DOI: 10.1590/s0021-75572006000800011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de atopia em crianças respiradoras bucais atendidas em centro de referência

Abstract: Objective: A mouth breather is someone who uses his/her oral cavity as main airway during breathing. This is a syndrome with several etiologies, but allergic rhinitis plays a key role due to its high prevalence. The aim of this study was to assess the presence of atopy among mouth-breathing patients referred to a tertiary care center in the metropolitan region of Belo Horizonte, Brazil.Methods: Cross-sectional, descriptive study carried out at Hospital das Clínicas of Universidade Federal de Minas Gerais. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 13 publications
(19 reference statements)
3
7
0
12
Order By: Relevance
“…The data obtained in this study corroborate the ISAAC, proving that 80.6% of adolescents with asthma (Table 1) had allergic rhinitis. Similar results were obtained in a survey conducted in the city of Belo Horizonte, which showed that among 560 children and adolescents with asthma, allergic rhinitis diagnosis was confirmed in 65% Allergic rhinitis is an important etiological factor of mouth breathing 10,19,20 . Papers related to the prevalence of mouth breathing are few in the literature and present percentages ranging around 58-75% 6 .…”
Section: Resultssupporting
confidence: 80%
“…The data obtained in this study corroborate the ISAAC, proving that 80.6% of adolescents with asthma (Table 1) had allergic rhinitis. Similar results were obtained in a survey conducted in the city of Belo Horizonte, which showed that among 560 children and adolescents with asthma, allergic rhinitis diagnosis was confirmed in 65% Allergic rhinitis is an important etiological factor of mouth breathing 10,19,20 . Papers related to the prevalence of mouth breathing are few in the literature and present percentages ranging around 58-75% 6 .…”
Section: Resultssupporting
confidence: 80%
“…Luane de Moraes Boton (1) , Ana Maria Toniolo da Silva (2) , Geovana de Paula Bolzan (3) , Eliane Castilhos Rodrigues Corrêa (4) , Angela Ruviaro Busanello (5) RESUMO Objetivo: verificar a atividade elétrica dos músculos orbiculares orais, masseteres e temporais no repouso, nas isometrias, labial e mastigatória, em crianças respiradoras nasais e respiradoras orais viciosas e obstrutivas, comparando-as. Métodos: foram estudadas 59 crianças, 15 respiradoras nasais (RN); 23 respiradoras orais viciosas (ROV) e 21 respiradoras orais obstrutivas (ROO).…”
Section: Estudo Eletromiográfico Dos Músculos Faciais De Respiradoresunclassified
“…Dentre as principais alterações estão deglutição alterada, mastigação ineficiente, fala distorcida, além de postura inadequada dos órgãos fonoarticulatórios e hipotonia muscular [1][2][3] . É fundamental o conhecimento da etiologia da respiração oral, a qual pode ser dividida em duas categorias: obstrutiva, decorrente de algum impedimento mecânico a passagem de ar, como desvio de septo, hiperplasia das tonsilas faríngeas ou palatinas (adenóide e/ou amígdala) 4 ; e não obstrutiva ou viciosa, quando ocorre por flacidez dos órgãos fonoarticulatórios ou por simples hábito 5,6 . Considerando os fatores desencadeantes da respiração oral e vários estudos 3,5,6 que destacam a importância do diagnóstico da mesma, é que surgiu o interesse por esta pesquisa.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The literature indicates that any factor that leads to an upper airway (UA) obstruction, such as septum deviation, pharyngeal or palatine tonsil hypertrophy (adenoids and/or tonsils) 3 , or even due to sagging on speech organs and simple parafunctional habits, causes nasal breathing to be replaced by mouth breathing 4 .…”
Section: Introductionmentioning
confidence: 99%